2016
DOI: 10.1021/acs.jcim.6b00091
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Dynamics Simulations Elucidate Conformational Dynamics Responsible for the Cyclization Reaction in TEAS

Abstract: The Mg-dependent 5-epi-aristolochene synthase from Nicotiana tabacum (called TEAS) could catalyze the linear farnesyl pyrophosphate (FPP) substrate to form bicyclic hydrocarbon 5-epi-aristolochene. The cyclization reaction mechanism of TEAS was proposed based on static crystal structures and quantum chemistry calculations in a few previous studies, but substrate FPP binding kinetics and protein conformational dynamics responsible for the enzymatic catalysis are still unclear. Herein, by elaborative and extensi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 50 publications
(73 reference statements)
2
20
0
Order By: Relevance
“…In amorphadiene synthase, the aromatic phenylalanine residue (residue in the same position of Y523 of Pam Tps1) was similarly involved in positioning of the FPP substrate in the active site, which subsequently stabilized the carbocation intermediates 84 . A similar observation was also reported by Zhang et al 85 with Nicotiana tabacum 5-epi-aristolochene synthase (TEAS) that catalyzed the cyclisation of FPP into bicyclic 5- epi -aristolochene. Mutational analysis of the aromatic amino acids proved the essential role of these residues in the active site for stabilization of the carbocation intermediates 79 , 85 .…”
Section: Resultssupporting
confidence: 84%
See 1 more Smart Citation
“…In amorphadiene synthase, the aromatic phenylalanine residue (residue in the same position of Y523 of Pam Tps1) was similarly involved in positioning of the FPP substrate in the active site, which subsequently stabilized the carbocation intermediates 84 . A similar observation was also reported by Zhang et al 85 with Nicotiana tabacum 5-epi-aristolochene synthase (TEAS) that catalyzed the cyclisation of FPP into bicyclic 5- epi -aristolochene. Mutational analysis of the aromatic amino acids proved the essential role of these residues in the active site for stabilization of the carbocation intermediates 79 , 85 .…”
Section: Resultssupporting
confidence: 84%
“…A similar observation was also reported by Zhang et al 85 with Nicotiana tabacum 5-epi-aristolochene synthase (TEAS) that catalyzed the cyclisation of FPP into bicyclic 5- epi -aristolochene. Mutational analysis of the aromatic amino acids proved the essential role of these residues in the active site for stabilization of the carbocation intermediates 79 , 85 . Positioning of GPP and FPP in the Pam Tps1 active site surrounded by these aromatic residues suggested that this docking analysis was rational and compatible with other crystal structures of terpene synthases.…”
Section: Resultssupporting
confidence: 84%
“…Residues outside the active site are thus likely to play an important role here. For instance, residues in helix 4 of the N-terminal domain appeared important for the functionality of some sesquiterpene synthases from Aquilaria crassna (Kumeta and Ito 2010) and a molecular dynamic study of TEAS points to the N-terminal domain in facilitating the stability of helix K and the ordering of the J-K loop (Zhang et al 2016). However, characterization in planta or using microorganisms may also be a contributing factor to this observed difference in germacrene D production (Salvagnin et al 2016) and the heat in the GC-MS may also have an impact (Andersen et al 2015).…”
Section: Important Residues Outside the Active Sitementioning
confidence: 99%
“…A recent computational analysis of the TEAS active site confirms the importance of this 'pre-Germacrene' conformation of FPP. 31 The 'U-shape' of FPP observed in the active site of our crystal structure is induced by the coordination of the pyrophosphate by the three Mg 2+ ions. The U shape is important for the conformation of the J-K loop, and more specifically, proper orientation of Y527.…”
Section: Structural Analysis Of Teas Bound With Small Moleculesmentioning
confidence: 77%